Rice Nutraceuticals and Bioactive Compounds: Extraction, Characterization and Antioxidant Activity: A Review - Zubair, Muhammad; Anwar, Farooq; Arshad, Insha; Malik, Shanza; Zafar, Muhammad N. (Combinatorial Chemistry & High Throughput Screening, 2023)
Rice (Oryza sativaL.), a cereal grass, belongs to the genus Oryzafrom the family Poaceae, which encompasses twenty-five species cultured in many countries of Asia, and partly in the rest of the world. From these species, two viz. Oryza sativa(O. sativa.) Asian rice and Oryza glaberrima. (O. glaberrima.) African rice are commonly found and the most widely consumed staple food by a large part of the human population in the world, especially in Asia due to their nutritional and nutraceutical prospects. Rice, a popular source of carbohydrates, also contains a good amount of dietary fiber, minerals (Ca, Zn, Se, P, K, Mg, Fe, and Mn), protein and vitamin B along with several other medicinally important bioactives such as tocols (α-tocopherols and α-tocotrienols) (ßsitosterol) phenolic acids, flavonoids (apiginine), and oryzanol (24-Methylenecylcoartanyl transferulate). Rice bran is a byproduct of the rice polishing industry and is valuable in terms of containing 15-20% high-value oil. Because of the natural antioxidants present in rice, several medicinal benefits and biological properties can be attributed to rice consumption. The nutrient profile of rice varies based on several factors, such as grains (white, brown, red, and black/purple), the extent of polishing, and the preparation method. Considering the importance of rice as a traditional diet rich in high-value bioactives, together with the existing gap of related information, it is worthwhile to assemble a comprehensive review that focuses on the detailed profile of valuable nutrients and high-value phytochemicals and biological activities of rice to explore its functional food and nutraceutical applications. This review attempts to provide collective information on the essential rice cereal for its nutritional and antioxidant potential.
Keywords: natural antioxidants